The influence of traditional Chinese landscape architecture on the image of small architectural forms in Europe - Żychowska, Maria; Ivashko, Yulia; Chang, Peng; Dmytrenko, Andrii; Kulichenko, Nataliia; Zhang, Xin Mu (Landscape Architecture and Art, 2021)
The article analyzes the influence of traditional Chinese landscape architecture on the shaping of European small architectural forms and the influence of European architecture on contemporary Chinese architectural practice. The purpose of the article is to identify the features of the architectural mutual influences of Chinese and European cultures. The method of historical analysis, the method of comparative analysis and the graphoanalytical method are used. The lack of identity between the Chinese and European gardens and the park with the pavilions is proved at the different hierarchical levels. Two groups of European Chinoiserie style pavilions have been identified: which give a false idea of Chinese architectural traditions and which represent a simplified version of those traditions. There is noticed the influence of the traditional Chinese approach to the architectural objects placement in the natural environment on the development of the contextualism concept in Western architecture (since the 1960s) which proclaims its purpose to preserve the natural beauty of the site through careful design that relates to its surroundings. The concept of contextualism is now widely used in the design of small architectural forms in the urban environment and in the design of the architectural environment in general, both in Europe and in China. This is a clear example of mutual enrichment with the ideas of two civilizations, each of which preserves its own culture.